Pemanfaatan Material Sisa Produksi Kayu Menjadi Produk Portable Notebook Stand (Studi Kasus UMKM CV. Restu Ibu, Sidayu, Gresik) (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2023)
Wood waste is unused and worthless pieces or remnants of wood production. Currently, wood waste is only used as charcoal or burned. The service team conducted a case study at CV in this community service. Mother's Blessing, District. Sidayu, Kab. Gresik. This activity requires further community service regarding the use of wood waste so that it becomes something valuable and useful. The method applied in this community service is to recognize several types of available wood materials and various forms of unused pieces of production leftovers—and continue with FGD, namely product design planning. As a result of this community service, it was found that wood waste left over from production could be reused into a useful and more valuable product, namely a portable notebook stand